Intraoperative neuromonitoring in traditional and miniinvasive thyroidectomy. A single center experience in 1652 nerve at risk. - Nisi, Piercosimo; Piva, Giovanna; Cozzani, Federico; Rossini, Matteo; Bonati, Elena; Madoni, Cristiana; Bignami, Elena Giovanna; Del Rio, Paolo (Acta Biomedica Atenei Parmensis, 2020)
Background: The injury of laryngeal recurrent nerve (RLN) is one of the most severe adverse event in thyroid surgery. The rate in literature is reported as 2-11% for transient palsy and 0,6-1,6% for permanent palsy (after 6 months from surgical procedure). Aim of the Study: The aim of this study was to describe the frequency of the injury of RLN in our hospital during thyroid surgery, in which the IONM was applied.  Materials and Methods: The patients undergoing thyroid surgery associated to Intraoperative Neuromonitoring (IONM were enrolled consecutively from 21/08/2014 to 30/08/2018. We collected data from I-IONM and not by Continuos IONM (C-IONM) because we have interrupted C-IONM after a case of cardiac arrest (15TH patient) during the APS  placement. Results: The utility of the intraoperative neuro-monitoring system was evaluated with the following statistical methods: Mann Withney U-test with independent samples,  T-samples with coupled samples, Wilcoxon signed sign test, Chi square test., Positive predictive value (PPV),  Negative predictive value (NPV),we considered the values for p